Effects of calcium silicate on the chemical and bioactive composition of Pleurotus ostreatus var. Florida - Cardoso, Rossana V.C. (2021)
Mushrooms are low-calorie foods with good quality proteins, vitamins and minerals, besides holding potential for some medicinal applications. In fact, mushrooms could be a source of many different nutraceuticals such as steroids, phenolic compounds, and others. Thus, they might be used directly in diet and promote health, taking advantage of the additive and synergistic effects of all the bioactive compounds present1. The edible mushroom Pleurotus ostreatus var. Florida known as "Hiratake" is one of the most consumed mushrooms in the world2, mainly due its easy cultivation, economic potential, nutritional quality, as well as therapeutic and biological properties. Silicon (Si) is known to play an important role in the mineral nutrition supplementation of mushrooms and plants, including increased productivity, through the availability of nutrients, increased biomass and resistance to biotic and abiotic stresses3. In this study, cultivated Pleurotus ostreatus var. Florida was supplemented with calcium silicate (0.5, 1, 2 and 4 %) and the effects of this supplementation on chemical and bioactive composition were evaluated. Ergosterol and vitamin D2 were determined by high performance liquid chromatography coupled to a UV detector; organic acids and phenolic compounds were determined by ultrafast liquid chromatography coupled to a photodiode array detector4. The supplementation with calcium silicate exerted remarkably positive effects in the evaluated parameters. Specifically, higher vitamin D2 contents were obtained in samples treated with 1% and 2% (866 and 862 μg/100 g dw). A similar increase was obtained in organic acids (5.15 g/100 g dw), considering the three identified compounds (oxalic, malic and fumaric acids) in samples treated with 0.5% of calcium silicate. The calcium silicate supplementation also increased the total phenolic compounds (protocatechuic acid, p-coumaric acid and cinnamic acid) relatively to the control sample. Calcium silicate supplementation was effective in improving the chemical profiles of P. ostreatus. Therefore, this practice may represent an effective way to increase the compounds of interest in different mushrooms.